War on drugs coverage journalists' trauma and newsroom support - Bael, Frances Dianne Salcedo 1998-; Villeza, Alliyah Marie; Khan, Rachel E. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2019)
This study has the objective to determine how trauma builds up in journalists covering President Rodrigo Duterte's "War on Drugs", and examine newsroom operations surrounding this issue, including the support and protocol given to the journalists. The said drug war is part of the anti-crime and anti-drug campaign of President Duterte which started as soon as he took office in June 2016, where more than 20,000 people have been killed. A number of journalists and photojournalists who cover the police/crime beat, specifically the drug war, have reported to be significantly disturbed due to exposure to traumatizing events-even accumulating psychological trauma. Using the lens of Hochschild'd theory of emotional labor, in-depth semi-structured interviews with journalists who fall under the said description plus their immediate supervisors were analyzed using interpretative phenomenological analysis to reveal how news organizations handle their reporters. The results showed that covering drug war indeed took a toll on both the physical and mental health of the journalists. On the other hand, newsroom had varying ways of managing their reporters-provision of protocol, casual conversation and consolation, and group counseling. However, only a few certain newsrooms have advanced, professional, and regular programs to address the distress or trauma their drug war reporters were experiencing. In essence, newsrooms' care for their journalists' mental health still has a lot of room for improvement.
Thesis
Includes bibliographical references.
Keywords: Journalists -- Mental health; Journalism -- Vocational guidance; Journalists -- Training of